2013
DOI: 10.1007/s00221-013-3788-6
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating visual–motor experience to probe for observation-induced after-effects in adaptation learning

Abstract: Observers can learn to move in novel, adapted environments after watching a learning or expert model. Although this is an effective practice technique, it is unclear how this learning is achieved and if observers update an internal model of their visual-motor environment, as shown through the presence of after-effects (i.e., negative carry-over effects when aiming in a normal environment following exposure to perturbed conditions). For such updating to occur via observational practice, it has been reasoned tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Although there is a consensus that shared mechanisms exist between action observation and execution [ 14 ], the role played by the motor system in observational learning is not clear [ 12 , 13 ]. Indeed, several studies have questioned the notion of motor-driven learning by observation, arguing instead that it is driven by perceptual and cognitive processes [ 40 42 ]. It is possible, therefore, that primary motor areas might be engaged during action observation [ 43 45 ], but their involvement might not be critical in shaping observational learning.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a consensus that shared mechanisms exist between action observation and execution [ 14 ], the role played by the motor system in observational learning is not clear [ 12 , 13 ]. Indeed, several studies have questioned the notion of motor-driven learning by observation, arguing instead that it is driven by perceptual and cognitive processes [ 40 42 ]. It is possible, therefore, that primary motor areas might be engaged during action observation [ 43 45 ], but their involvement might not be critical in shaping observational learning.…”
Section: Discussionmentioning
confidence: 99%
“…Such an assumption (i.e., no after-effects indicate no internal models) was used in a series of studies conducted by Hodges and colleagues (e.g., Larssen et al 2012;Lim et al 2014;Ong and Hodges 2010), in which observers who watched a model adapting to a novel visuomotor condition demonstrated substantial improvement in performance when they later performed a reaching task under the same visuomotor condition (referred to as "direct-effects"), but failed to demonstrate after-effects under a normal visuomotor condition. Based on these findings, Hodges and colleagues suggested that observational learning, which has been suggested to lead to the formation of an internal model (Brown et al 2010;Mattar and Gribble 2005), may not actually involve an internal model, and that physical practice may be required for the formation of an internal model.…”
mentioning
confidence: 99%
“…Similar to learning through physical practice, learning through observation involves high-order cognitive processes (Hodges et al, 2011;Lim et al, 2014;Maslovat et al, 2010;Vogt & Thomaschke, 2007). Although many similarities exist between the cognitive and neural processes supporting learning though physical and observational practice (Blandin et al, 1999;Boutin et al, 2010;Hodges et al, 2007;Vogt et al, 2007;Gardner, Aglinskas & Cross, 2017), here we show limits to this similarity.…”
Section: Individual Differences In Skill Learning Through Physical and Observational Practicementioning
confidence: 44%